A troubled heart: Mood disorder history longitudinally predicts faster cardiopulmonary aging in breast cancer survivorship - Madison, Annelise A.; Filatov, Marie; Andridge, Rebecca; Haas, Garrie; Povoski, Stephen P.; Agnese, Doreen M.; Lustberg, Maryam; Reinbolt, Raquel E.; Wesolowski, Robert; Williams, Nicole O.; Malarkey, William B.; Kiecolt-Glaser, Janice K. (PLOS ONE, 2023)
Objective Breast cancer survivors live longer due to more advanced cancer treatments; however, cardiovascular disease (CVD) is the leading non-cancer cause of death in breast cancer survivors. Previous studies have shown that depression is associated with an increased risk of CVD development. This study investigated whether depressive symptoms or mood disorder history, either independently or in combination with cardiotoxic treatments, predicted older cardiopulmonary age using a novel index–the Age Based on Exercise Stress Test (ABEST)–among breast cancer survivors. Methods Breast cancer survivors (N = 80, ages 26–72, stage I-IIIA) were assessed an average of 53 days (SD = 26) post-surgery, but before adjuvant treatment, and again an average of 32 (SD = 6) months thereafter. At both visits, they reported depressive symptoms on the Center for Epidemiologic Studies Depression Scale (CES-D), completed the Structured Clinical Interview for DSM-V, and engaged in an exercise stress test to obtain ABEST scores. Results Controlling for treatment type, age, education, trunk fat, antidepressant use, and time between visits, longitudinal analyses showed that breast cancer survivors with a mood disorder history had worsening ABEST scores over time, compared to their peers without this history (p = .046). Change in physical activity between Visits 1 and 2 did not mediate this relationship (95% CI: -0.16–0.51). Ancillary analyses provided some additional support for the primary finding, such that those with a mood disorder history trended toward greater decreases in Vo2max, although results were marginally non-significant (p = .095). There were no cross-sectional relationships between depressive symptoms or mood disorder history and ABEST scores (ps>.20). Treatment type did not modulate observed relationships (ps>.22). Conclusions Breast cancer survivors with a mood disorder history may experience faster cardiopulmonary aging compared to their peers without such a history, raising risk for CVD.